Comparison of the gut microbiota of college students with the nine balanced and unbalanced traditional Chinese medicine constitutions and its potential application in fecal microbiota transplantation - Huang, Qinhong; Yang, Lihui; Cai, Guannan; Huang, Yongdie; Zhang, Shian; Ye, Zhenwei; Yang, Jing; Gao, Chuhui; Lai, Jiaxuan; Lin, Lyu; Wang, Jihui; Liu, Ting (Frontiers in Microbiomes, 2023)
Fecal microbiota transplantation (FMT) has been tested for the prevention and treatment of various intestinal and extra-intestinal diseases, but its efficacy is not stable, which may be due to lack of an optimized method to screen high quality donors. In addition, the low efficiency and high cost of donor screening are also obstacles to the clinical application of FMT. In this study, we tested the use of constitution theory of the Traditional Chinese Medicine (TCM) to efficiently screen high-quality FMT donors. College student volunteers were divided into balanced constitution (BC) and eight unbalanced TCM constitutions (UBCs), and gut microbiota profiles of each UBC were compared with that of BC. Next, the success rate of qualified donors of BC and UBC volunteers was also compared.Finally, anti-obesity effect of FMT using fecal microbiota of BC and UBC donors were tested on high-fat-diet induced obesity mice. Results showed that gut microbiota of BC and UBC volunteers were significantly different. Among the volunteers, those with BC had a higher proportion of qualified FMT donors than that with UBC. Moreover, mice experiment showed that fecal microbiota of BC and UBC volunteers conferred different anti-obesity effects. Overall, TCM constitution could be a reference for FMT practice. Our study provides a new idea using TCM constitution theory to efficiently screen high quality FMT donors.